Anomalous size effect of impact resistance in carbon nanotube film - Wei Zhang; Kailu Xiao; Dongmei Hu; Chenguang Huang; Xianqian Wu (Materials Today Advances)
Dynamic mechanical behavior and size-related impact resistance of CNT films are studied by employing laser-induced projectile impact test (LIPIT) and coarse-grained molecular dynamics (CGMD) simulation. The energy dissipation mechanisms of the CNT films are investigated via CGMD simulations. An evident anomalous thickness-dependent effect is directly observed in the experiment, consistent with simulation phenomena. The mechanisms underlying this anomalous thickness-dependent effect are investigated at the atomic scale. The disparities between experiments and simulations are discussed. Our analysis of energy dissipation modes, deformation behaviors during impact, and impact area reveals that kinetic energy change predominantly governs the deformation mode. Meanwhile, a plugging failure mode near the exit face of CNT film is identified at high impact velocity (∼160 m/s), leading to a deterioration in impact resistance and a corresponding reduction in SEA with increasing CNT film thickness. These findings provide a feasible strategy for the protection design of CNT ﬁlm in broaden protective application scenarios.